Direito Penal do Inimigo : o Estado na sua constante instrumentalização social - Kruber, Carlos José Pereira (2014)
This dissertation, suitable to the area of concentration Criminal System and Violence , with emphasis on the research line on "Violence, Crime and Public Safety", of the Masters in Criminal Sciences at Pontifical Catholic University of Rio Grande do Sul, was aimed to understand, from a transdisciplinary vision, the consequences of the exploitation of the individual and of the Criminal Law in the Contemporaneous State in face of adoption of Criminal Law of the Enemy . It was highlighted, initially, the study of the practices of choice of certain subjects to be considered as enemies of the State in the current Society of Risk , as defined by Beck. Then, the similar and previous theoretical positions were checked that support the thesis of Jakobs, as well as the Brazilian situation relating to the terrorism. It is known that Jakobs thesis has been introduced in several countries, mainly after the terrorist attack of September 11, in the United States, however there is a growing tendency that Jakobs thesis may provide new ways to think and act against the criminality, converted into a conception that is no longer limited to a simple description, unlike, postulate and require the exclusion and marginalization of the enemies of the system (dominant). An analysis has been taken about the welfare society, individualism as social classification and protection of the new legal assets, justified by the social insecurity in light of a new criminality as well as the search for preventive policies or security at all costs, as a way of social clamor propelled by the media and by fear. Finally, there was a reflection on the possibility of the instrumentalization of the individual and of the Criminal Law in view of Jakobs thesis in the current contemporaneous society as a justification of combat the enemy.